A STUDY ON MULTICULTURAL UNIVERSITY STUDENTS’ MOTIVATION IN SPEAKING ENGLISH: PROBLEMS AND SOLUTIONS - Nisa Usy Syakiroh; Syifaur Rahma Aulia; Frilli Afrillia; Heni Carolyn; Ana Asidikia; Lestari Budianto (PROJECT (Professional Journal of English Education), 2024)
The ability to speak English is a skill that is difficult to master. Some problems must be faced by someone who wants to master these skills, including multicultural students. This research aims to investigate the problems faced by multicultural students and find solutions that can be applied to deal with these problems. This research uses descriptive qualitative research methods. This research involved three students from various majors and cultures. This research data was collected through observation and interviews. The results of this research show that there are three problems, namely those related to a less supportive language environment, lack of self-confidence, and lack of opportunities to practice speaking English. The results of this research also reveal the existence of solutions to these problems. The solutions are to form a community, find practice friends, and submit mandatory and non-compulsory courses to campus. However, this research is limited in the number and variety of participants. Therefore, it is recommended for future research to conduct research on similar topics but to increase the variety of research participants.